Improving Learning Outcomes of PAI & BP Zakat Material Through Problem Based Learning Model for Class V Students of Sd Negeri 010 Tambusai - Nasution, Zainul Mahdi; Nurwahidah, Nurwahidah; Suanto, Suanto (STKIP Rokania Pasir Pangaraian, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education and Budi Pekerti (PAI & BP) on zakat material through the Problem Based Learning (PBL) model in class V SD Negeri 010 Tambusai. This research is a Classroom Action Research (PTK) conducted in three stages, namely pre-cycle, cycle I, and cycle II. The research subjects were 15 grade V students in the 2023 school year. Data were collected through learning outcome tests and observations of student engagement in learning. The results showed that the application of the PBL model can significantly improve student learning outcomes from pre-cycle to cycle I and then to cycle II.